PROPORSI PENGGUNAAN BERBAGAI JENIS DAUN TANAMAN UNTUK PAKAN TERNAK KAMBING PADA LOKASI DAN KETINGGIAN BERBEDA DI WILAYAH MALANG RAYA - Susanti, Sri; Marhaeniyanto, Eko (Universitas Tribhuwana Tunggadewi, 2017)
This research to inventory of tree foliages leaves and proportion of potential utilization as animal feed on the different location and altitudes in Malang Raya. For the long term, the study aims to assess the potential of several types of tree foliages leaves as feed in order to provide quality animal feed, relatively inexpensive for sustainable livestock development.The research method was survey study and conducted in five districts centers goat in Malang Raya. The results showed that there were 30 types of forage used as goat feeds, both leaves of tree foliages and shrubs, or grasses, crop residues and the others. Most forages (73%) were the leaves of tree foliages and shrubs, both legumes and non legumes. Tree foliage leaves were more used as goat feeds in the study area with higher altitude, whereas in the study by a lower altitude also utilize grasses and crop residues. The leaves of tree foliages used by the respondents in the study area were Paraserianthes falcataria, Gliricidia sepium, Artocarpus heterophyllus, Leucaena leucocephala and Calliandra calothyrsus. Paraserianthes falcataria most widely used in Klampok- Singosari (88.3%).The proportion of use Calliandra calothyrsus ranged 32-98%, while Gliricidia sepium 58-98%, both were most widely used in Argoyuwono-Ampelgading. Artocarpus heterophyllus most widely used in Wajak (90.3%), whereas Leucaena leucocephala leaf used by all respondents (100%) in Sumberdem-Wonosari. For further research is necessary to evaluate the quality of a potential tree foliage leaves in Malang, in order to provide quality animal feed through supplementation technology to sustainable livestock development.